Values and emotions in contemporary Polish reportages - Bogołębska, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
For the sake of the present analysis, definitions of values and emotions or affects are taken from Aristotle’s Rhetoric and from modern typologies of emotions. Selected Polish reportages of the 20th and 21st century have been chosen to illustrate the rhetoric of emotion. The paper elaborates on the following affects: anger, compassion, indignation, ambition, fear, courage, shame, sympathy, boredom, sadness, disappointment, admiration, respect. Examples of persuasive strategies (ethos and pathos) as well as linguistic expression of emotions are also taken into consideration.